Urgensi Persepsi Peserta Didik dalam Menilai Kompetensi Dosen - Irawan, Vaesol Wahyu Eka (MOMENTUM : Jurnal Sosial dan Keagamaan, 2018)
Perception is one's ability to organize observations, such as: the ability to differentiate, the ability to group, and the ability to focus. Teachers' lesson is the unanimity of knowledge, honesty and attitudes of tangible action as an instructional agent that becomes one of the important factors to achieve the learning objectives and the other is one of the factors that are in the process of achieving the learning objectives and others. Education, teaching experience, and last teaching. Pedagogic competence isthe ability of understanding of learners, planning and implementation of learning, evaluation of learning outcomes, and development of learners to actualize the various potentials it has. The pedagogic competence includes: Knowing the students, mastering theories about education, lesson materials, various techniques and learning methods, developing learning implementation plans (RPP) and evaluating the learning process and outcomes. Professional is a work or activity undertaken by a person and a living source of income that requires expertise, skill or skill that meets certain standards of quality or norm and requires professional education. Personality competence is a competence of qualities that appear from within and from the outside of the individual. And also a daily attitude of a lecturer towards students